2007
DOI: 10.1128/aem.03003-06
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Two Library-Independent Microbial Source Tracking Methods To Identify Sources of Fecal Contamination in French Estuaries

Abstract: In order to identify the origin of the fecal contamination observed in French estuaries, two libraryindependent microbial source tracking (MST) methods were selected: (i) Bacteroidales host-specific 16S rRNA gene markers and (ii) F-specific RNA bacteriophage genotyping. The specificity of the Bacteroidales markers was evaluated on human and animal (bovine, pig, sheep, and bird) feces. Two human-specific markers (HF183 and HF134), one ruminant-specific marker (CF193), and one pig-specific marker (PF163) showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
86
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(95 citation statements)
references
References 57 publications
(70 reference statements)
8
86
1
Order By: Relevance
“…Overall, the sensitivity (100% for faecal and wastewater samples both) and specificity (87%) of the HBac marker assay was comparable with the sensitivity and specificity reported in the studies conducted in the USA (sensitivity 50Á85% and 100% for faecal and wastewater samples, and specificity 86Á100%; Bernhard & Field 2000b;Carson et al 2005), in France (sensitivity 86Á98% and specificity 94Á99%; Gourmelon et al 2007) and in Australia (sensitivity 100% and specificity 100%; Ahmed et al 2008a, b). In contrast, the sensitivity of the RBac marker was 85% and specificity 65%, which is considerably lower when compared with the studies conducted in the USA (97Á100% sensitivity, 100% specificity; Bernhard & Field 2000b) and in Australia (sensitivity 100% and specificity 97%; Ahmed et al 2008a), but similar to the results reported for samples collected in France (sensitivity 100% and specificity roughly 67Á77%; Gourmelon et al 2007). Poor specificity of the marker in the current study could be related to the relatively high number of marsupial samples (12%) and/or regional differences.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Overall, the sensitivity (100% for faecal and wastewater samples both) and specificity (87%) of the HBac marker assay was comparable with the sensitivity and specificity reported in the studies conducted in the USA (sensitivity 50Á85% and 100% for faecal and wastewater samples, and specificity 86Á100%; Bernhard & Field 2000b;Carson et al 2005), in France (sensitivity 86Á98% and specificity 94Á99%; Gourmelon et al 2007) and in Australia (sensitivity 100% and specificity 100%; Ahmed et al 2008a, b). In contrast, the sensitivity of the RBac marker was 85% and specificity 65%, which is considerably lower when compared with the studies conducted in the USA (97Á100% sensitivity, 100% specificity; Bernhard & Field 2000b) and in Australia (sensitivity 100% and specificity 97%; Ahmed et al 2008a), but similar to the results reported for samples collected in France (sensitivity 100% and specificity roughly 67Á77%; Gourmelon et al 2007). Poor specificity of the marker in the current study could be related to the relatively high number of marsupial samples (12%) and/or regional differences.…”
Section: Discussionsupporting
confidence: 71%
“…Both ruminant and human-associated Bacteroidales markers (RBac and HBac) tested positive for their target host organisms, however, they also displayed cross-reactivity with brush-tail possums (as confirmed from sequencing for HBac), other marsupials, gulls and rabbits. Bacteroidales markers have been widely used overseas and have shown limited crossreactivity with other organisms*HBac markers have been detected from dog (Carson et al 2005;Kildare et al 2007;Harwood et al 2009), cat (Kildare et al 2007) and chicken faeces (Carson et al 2005;Kildare et al 2007;Gourmelon et al 2007;Harwood et al 2009), and the RBac marker has detected in faeces from chickens (Ahmed et al 2008a), horse (this study and V. Harwood, personal communication), pigs (Gourmelon et al 2007) and humans (Gourmelon et al 2007). Overall, the sensitivity (100% for faecal and wastewater samples both) and specificity (87%) of the HBac marker assay was comparable with the sensitivity and specificity reported in the studies conducted in the USA (sensitivity 50Á85% and 100% for faecal and wastewater samples, and specificity 86Á100%; Bernhard & Field 2000b;Carson et al 2005), in France (sensitivity 86Á98% and specificity 94Á99%; Gourmelon et al 2007) and in Australia (sensitivity 100% and specificity 100%; Ahmed et al 2008a, b).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…There are promising bird markers, however, which come from Catellicoccus 16S rRNA gene markers (Lu et al 2011;Green et al 2012;Ryu et al 2012a, b), and one demonstrated to identify Sandhill Crane excreta (Ryu et al 2012a, b) was used and supported in the current study (Table 1). A further line of evidence comes from the limited detection of Bacteroidetes in Sandhill Crane and Snow Goose excreta compared to other animal/human fecal sources, which has also been reported for other avian species (Lu et al 2007(Lu et al , 2008(Lu et al , 2009Gourmelon et al 2007;Dubinsky et al 2012). When including the high occurrence of likely human pathogenic C. jejuni from Sandhill Crane excreta, but lack of other pathogens identified during the current study (Table 1; Lu et al 2013), we now focus on the lines of evidence of this fecal pollution within Platte river water and sediments.…”
Section: Key Markers Of Crane Pollutionmentioning
confidence: 90%
“…Further testing is required to determine whether the engineered bacteriophage can be used for field-deployment. Although many different types and phage strains have been isolated from the environment, and while the application of these bacteriophage for the purposes of gene typing and water quality indication have been well studied [41][42][43], the application of isolated bacteriophage or engineered bacteirophage for bioremediation has not yet explored. Therefore the study reported here offers initial data and analysis useful to the applications of bacteriophage for uranium bioremedia tions at Cr and U contaminated sites such as those managed by the US Department of Energy.…”
Section: Discussionmentioning
confidence: 99%